Exploring happiness : from Aristotle to brain science / Sissela Bok. - Bok, Sissela (Yale University Press, 2010)
Examines the nature of happiness, discussing how it has been treated in philosophy and religion and by the modern disciplines of psychology, economics, and neurocience, and considers the place of individual happiness within the context of modern life.